Evaluation of Pharmacology and Pathophysiology Knowledge of Epilepsy among Senior Pharmacy Students: A Single Center Experience - Nasser M. Alorfi; Ahmed M. Ashour; Hanouf S. Bafhaid; Fahad S. Alshehri (Medicina, 2023)
Background and Objectives: Epilepsy is a chronic disease that causes substantial morbidity and mortality. Pharmacists represent an integral role in managing patients with epilepsy. The aim of this study was to evaluate the level of knowledge about the pharmacology and pathophysiology of epilepsy among senior pharmacy students. Materials and Methods: Cross-sectional study using a designed questionnaire to measure the pharmacological and physiological knowledge of senior pharmacy students regarding epilepsy who are studying at Umm Al-Qura University, Makkah, Saudi Arabia, from August to October 2022. Results: A total of 211 senior clinical pharmacy students responded to the questionnaire. The majority of the respondents were 4th year pharmacy students. The numbers of female and male participants were equal (106 and 105 students, respectively). The participants represented an acceptable level of knowledge about the pathophysiology aspects of epilepsy, with a mean total score of 6.22 ± 1.9 out of a maximum score of 10. The respondents reported that epilepsy could be due to genetic predisposition combined with environmental conditions (80.1%) or brain stroke (17.1%). Regarding the respondent knowledge about the pharmacology of epilepsy, the total score was 4.6 ± 2.1 (maximum attainable score: 9). Conclusions: The majority of pharmacy students had knowledge about the pathophysiology concept of the disease; however, low knowledge was shown by the respondents regarding the pharmacology of epilepsy. Thus, there is a need to identify better strategies to improve students’ education.